Mathematical analysis of heat balance model for the bubble growth in the subcooled boiling flow - Xiaomeng Dong (Elsevier, 2021)
Subcooled boiling flow is a typical phenomenon of a high efficiency of heat transfer in the nuclear reactor. Bubble characteristic sizes are important parameters for the mechanism investigation of subcooled boiling flow. Compared to the empirical correlation and force analysis model, the heat balance model is an effective method to describe the growth of bubble and calculate the bubble maximum diameter. After a wide investigation of the law of bubble growth, some researchers concluded that the bubble diameter would increase all the time during the process. However after a detailed mathematical analysis by use of Squeeze Theorem, new model is developed for the bubble growth model according to heat balance theory in this paper. Compared to the traditional Unal's model, new model indicates the existence of local bubble maximum diameter during the bubble growth's process. In addition, a key group value is provided for the area ratios of different heat fluxes. Several databases are used for validation of the new model. The errors are around 20% which show the accuracy of the new method.